Controlling Vaname Shrimp (Litopenaeus Vannamei) Raw Material Inventories (Case Study at PT. Grahamakmur Ciptapratama Sidoarjo) - Iffan Maflahah; Amalia Wahyu Pratiwi; Asfan (Universitas Muhammadiyah Sidoarjo, 2020)
Raw material inventory control is used to place orders and ensure that shrimp raw materials arrive in a timely manner in accordance with consumer demand. This will expedite the course of the production process. This research was conducted at PT. Grahamakmur Ciptapratama Sidoarjo with the aim of knowing and analyzing the control of raw red ginger in frozen shrimp products. The method used is the Economic Order Quantity (EOQ) Method with the Lot For Lot (LFL) Technique. In addition, safety stock analysis, Maximum Inventory, warehouse capacity and Reorder Point analysis were carried out. The results of the study showed that inventory costs using the EOQ technique were lower than the company method or using the LFL technique. The EOQ technique produces an inventory cost of IDR 292,591.00 in 2017 with an order frequency of 105 times and in 2018 of IDR 289,750.00 with a booking frequency of 116 times. In the LFL technique inventory costs are more expensive, but the planning technique in the LFL method can be applied by companies in anticipation of raw material inventory if there is a small inventory. If the company applies the EOQ method, the company purchases raw materials in a larger amount, but the warehouse capacity in the company can still be met, this can be seen from the calculation of Maximum Inventory and warehouse capacity.